2014
DOI: 10.4155/bio.14.283
|View full text |Cite
|
Sign up to set email alerts
|

2014 White Paper on Recent Issues in Bioanalysis: A Full Immersion in Bioanalysis (Part 3 – LBA and Immunogenicity)

Abstract: The 2014 8th Workshop on Recent Issues in Bioanalysis (8th WRIB), a 5-day full immersion in the evolving field of bioanalysis, took place in Universal City, California, USA. Close to 500 professionals from pharmaceutical and biopharmaceutical companies, contract research organizations and regulatory agencies worldwide convened to share, review, discuss and agree on approaches to address current issues of interest in bioanalysis. The topics covered included both small and large molecules, and involved LCMS, hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…At the 2014 Workshop, it was concluded that drug tolerance is a frequently encountered challenge among relatively high dosed therapeutics with a long half-life [10]. However, a great deal of progress had been made within the bioanalytical community in the previous decade concerning the technical hurdles, possibly due to the number of post-marketing requirements from health authorities, thus making drug tolerance a routine objective for all clinical testing.…”
Section: Immunogenicity (Ada) Assays: Drug Tolerancementioning
confidence: 99%
See 3 more Smart Citations
“…At the 2014 Workshop, it was concluded that drug tolerance is a frequently encountered challenge among relatively high dosed therapeutics with a long half-life [10]. However, a great deal of progress had been made within the bioanalytical community in the previous decade concerning the technical hurdles, possibly due to the number of post-marketing requirements from health authorities, thus making drug tolerance a routine objective for all clinical testing.…”
Section: Immunogenicity (Ada) Assays: Drug Tolerancementioning
confidence: 99%
“…It is likely that changes in PK profiles will occur as new, more specific critical reagents become available with the evolution of methods. It is not necessary to have the same result from different PK assays, but rather that there should be a scientific understanding of the species that the assays are measuring so that results can be interpreted appropriately [10]. Continued discussions in 2015 recommended that when there are differences in concentration future science group Special Feature Garofolo & Savoie results between two LBA platforms that had been previously cross-validated, an investigation would be needed to understand the reasons for the differences.…”
Section: Cross-validation (Lba)mentioning
confidence: 99%
See 2 more Smart Citations
“…During validation, understanding the effect of target interference and anti-drug antibodies (by utilizing a surrogate control) should be evaluated at a minimum. As bioanalytical scientists, we must strive to fully characterize our assays, to understand their strengths and limitations (14). While these experiments require time and often go above and beyond current regulatory requirements, the result will be robust bioanalytical methods with easily translatable and defendable data.…”
Section: What Are You Measuring?mentioning
confidence: 99%